PERFORMANCE DIESEL DUAL FUEL ENGINE ON ADDITIONAL COCONUT SHELL OIL - Nugroho, Agung; Winanto, Mohfan Juni; Syafa'at, Imam; Ratnani, Rita Dwi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
Fuel alternative diesel was developed aiming to develop environmentally friendly alternative fuels in Indonesia. The purpose of this study was to determine the physical properties and quality of diesel produced from coconut shell liquid smoke, B20, and B40. The quality and physical properties of diesel in question were tested in terms of its Calorific Value, Viscosity, Density, and Cetane Number test. Based on the engine performance testing, the parameters sought were torque, power, and specific fuel consumption. In this case, the testing of the physical properties of diesel was conducted through the comparison of the fuel used, among others, the highest torque value was obtained at 32.415 Nm on diesel fuel for the engine shaft rotation of 1980 rpm with the mass load of 9.6 kg. Furthermore, fuel consumption specific was obtained from diesel fuel with the largest rotation of 3548 rpm using 337.4 g/kWh, while the lowest value was obtained from diesel B40 with a torque value of 24.702 Nm. In this case, the lowest mass fuel consumption specific (SFC)) was found in coconut shell oil mixture with the largest rotation of 1520 rpm using 40.9 g/kWh. The conclusion made was that the addition of coconut shell oil in diesel can reduce energy because the calorific value decreased, as evidenced by the addition of coconut shell oil causing the engine performance to decrease.